The effects of beta-hydroxy-beta-methyl butyrate supplementation in surgical patients: a systematic review and meta-analysis of randomized controlled trials - Hu, Yan-Ge; Shi, Ji-Heng; Yu, Da-Xing; Huang, Hui-Bin (Frontiers in nutrition (Lausanne), 2025)
Beta-hydroxy-beta-methylbutyrate (HMB) is a nutritional supplement that has demonstrated favorable effects on restoring muscle mass. However, evidence to support its use in patients underlying surgery remains unclear. We aimed to conduct a systematic review and meta-analysis of HMB in this population to ascertain its effect. We searched PubMed, EMBASE, Web of Science, the China National Knowledge Infrastructure, Wanfang, and the Cochrane Library for randomized controlled trials (RCTs) focused on surgical patients receiving HMB compared to controls. The last search was March 15, 2025. Length of stay (LOS) and postoperative complications were the primary outcomes. We assessed study quality and performed subgroup analysis, sensitivity analysis, and the GRADE system to explore potential heterogeneity. Eleven RCTs with 575 patients were included. There are some differences in study design, HMB protocols, and muscle measurements among these trials. Overall, HMB significantly reduced the hospital LOS (MD -0.90 days; 95% CI, -1.79 to -0.01; = 0%, = 0.05) and postoperative complications (RR 0.50; 95% CI, 0.32 to 0.79; = 0%, = 0.003). These findings were confirmed in most subgroup and sensitivity analyses. As to muscle measurements, the HMB group had significantly more mid-arm muscle-circumference ( = 0.05), appendix skeletal muscle mass ( = 0.03) and 6-min walking distances ( = 0.007), but had similar changes in skeletal muscle mass and lean body mass. Regarding nutritional status, compared to the control group, the HMB group did not show significant improvement from baseline after treatment, including body weight, body mass index, serum albumin, and total albumin ( -values from 0.10 to 0.63). HMB supplement seems to significantly improve hospital LOS and postoperative complications, as well as some outcomes of muscle measurements and physical function. However, due to the significantly heterogeneity among the included studies, more well-designed RCTs are needed to confirm our findings.